Mineralocorticoid Receptor-Dependent Impairment of Baroreflex Contributes to Hypertension in a Mouse Model of Primary Aldosteronism - Shi, Luo; Yuan, Fang; Wang, Xuefang; Wang, Ri; Liu, Kun; Tian, Yanming; Guo, Zan; Zhang, Xiangjian; Wang, Sheng (Frontiers in Physiology, 2019)
Primary aldosteronism (PA) is the most common cause of secondary hypertension. The paucity of good animal models hinders our understanding of the pathophysiology of PA and the hypertensive mechanism of PA remains incompletely known. It was recently reported that genetic deletion of TWIK-related acid-sensitive potassium-1 and -3 channels from mice (TASK-/-) generates aldosterone excess and mild hypertension. We addressed the hypertensive mechanism by assessing autonomic regulation of cardiovascular activity in this TASK-/- mouse line that exhibits the hallmarks of PA. Here, we demonstrate that TASK-/- mice were hypertensive with 24-hour ambulatory arterial pressure. Either systemic or central blockade of the mineralocorticoid receptor (MR) markedly reduced elevated arterial pressure to normal level in TASK-/- mice. The response of heart rate to the muscarinic cholinergic receptor blocker atropine was similar between TASK-/- and wild-type mice. However, the responses of heart rate to the β-adrenergic receptor blocker propranolol and of arterial pressure to the ganglion blocker hexamethonium were enhanced in TASK-/- mice relative to the counterparts. Moreover, the bradycardiac rather than tachycardiac gain of the arterial baroreflex was significantly attenuated and blockade of MRs to a large degree rescued the dysautonomia and baroreflex gain in TASK-/- mice. Overall, the present study suggests that the MR-dependent dysautonomia and reduced baroreflex gain contribute to the development of hyperaldosteronism-related hypertension.